THE PECULIARITY OF THE RUSSIAN STRESS - Parpiyev Odil Olimovich (Modern American Journals, 2025)
The article deals with the peculiarities of Russian accent. In Russian, stress is by its very nature a phonetic phenomenon, but it is also associated with morphology. Both aspects are considered – the structure of a phonetic word and stress as a structural component of a grammatical word: mobility, types of stress, diversity, and evolutionary processes.
Keywords: stress, setting, syllable, pronunciation, mobile, fixed, equal, variability.